Pengaruh Pelatihan Kader Kesehatan Jiwa Terhadap Pengetahuan dan Ketrampilan Kader di Wilayah Kerja Puskesmas Menteng - Missesa Missesa (POLITEKNIK KESEHATAN KEMENKES PALANGKA RAYA, 2022)
Nurses as health workers are responsible for overcoming mental health problems by working with mental health cadres. This study aims to determine the effect of mental health cadre training on the knowledge and skills of cadres in the working area of the Menteng Health Center. The research method used is quantitative research